El nivel de conceptualization: Una clase de respuestas verbales controladas por la contingencias de reforzamiento - Lopez R., Florente; Ribes I., Emilio (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
An hypothesis w as formulated concerning the possibility o f applying S-R principles to the study o f conceptual behavior. A program of variable ratio reinforcement was employed with a group of school children to determine if the levels o f conceptual response, functional and concrete, could be changed as such responses are measured by a verbal version of the Gardner Object Classification Test. The data did not confirm the hypothesis. Nevertheless, arguments are presented to explain the results without rejecting the initial hypothesis which suggests possibilities for future research on this problem.